Age hardening responses of as-extruded Mg-2.5Sn-1.5Ca alloys with a wide range of Al concentration. (1st February 2020) - Huang, Qiuyan; Liu, Yang; Zhang, Aiyue; Jiang, Haoxin; Pan, Hucheng; Feng, Xiaohui; Yang, Changlin; Luo, Tianjiao; Li, Yingju; Yang, Yuansheng
Abstract: This article aims to explore the age hardening responses of both as-extruded and as-aged Mg-2.5Sn-1.5Ca- x Al alloys ( x  = 2.0, 4.0 and 9.0 wt%, termed TXA322, TXA324 and TXA329, respectively) through microstructural and mechanical characterization. Results indicate that grain size of as-extruded TXA322, TXA324 and TXA329 alloys were ∼ 16 μm, ∼ 10 μm and ∼ 12 μm, respectively. A number of < a > and < c + a > dislocations were observed in all the as-extruded samples. Guinier – Preston (GP) zones were evidently identified in TXA322 alloy, while only a small number of Mg17 Al12 phases existed in both TXA324 and TXA329 alloys. An aging treatment facilitated the precipitation of a high number density of GP zones within the matrix of TXA322 alloy. In contrast, no obvious nano-precipitates were in as-aged TXA324 alloy. Numerous nano-Mg17Al12 phases were formed through a following aging treatment in TXA329 alloy. In terms of mechanical properties, it is apparent that an increment in ultimate tensile strength of ∼ 46 MPa and ∼ 40 MPa was yielded in peak-aged TXA322 and TXA329 alloys, while no obvious variations in UTS were present in peak-aged TXA324 alloy, in comparison with the as-extruded counterparts.